Pannexin 1 inhibits rhabdomyosarcoma progression through a mechanism independent of its canonical channel function. (November 2018) - Xiang, Xiao; Langlois, Stéphanie; St-Pierre, Marie-Eve; Barré, Jessica; Grynspan, David; Purgina, Bibianna; Cowan, Kyle
Abstract Rhabdomyosarcoma (RMS) is an aggressive soft tissue sarcoma of childhood thought to arise from impaired differentiation of skeletal muscle progenitors. We have recently identified Pannexin 1 (PANX1) channels as a novel regulator of skeletal myogenesis. In the present study, we determined that PANX1 transcript and protein levels are down-regulated in embryonal (eRMS) and alveolar RMS (aRMS) patient-derived cell lines and primary tumor specimens as compared to differentiated skeletal muscle myoblasts and tissue, respectively. While not sufficient to overcome the inability of RMS to reach terminal differentiation, ectopic expression of PANX1 in eRMS (Rh18) and aRMS (Rh30) cells significantly decreased their proliferative and migratory potential. Furthermore, ectopic PANX1 abolished 3D spheroid formation in eRMS and aRMS cells and induced regression of established spheroids through induction of apoptosis. Notably, PANX1 expression also significantly reduced the growth of human eRMS and aRMS tumor xenografts in vivo. Interestingly, PANX1 does not form active channels when expressed in eRMS (Rh18) and aRMS (Rh30) cells and the addition of PANX1 channel inhibitors did not alter or reverse the PANX1-mediated reduction of cell proliferation and migration. Moreover, expression of channel-defective PANX1 mutants not only disrupted eRMS and aRMS 3D spheroids, but also inhibited in vivo RMS tumor growth. Altogether our findings suggest that PANX1 alleviates RMS malignant properties in vitro and in vivo through a process that is independent of its canonical channel function.